Reduced premovement positivity during the stimulus‐response interval precedes errors: Using single‐trial and regression ERPs to understand performance deficits in ADHD. (12th May 2019) - Burwell, Scott J.; Makeig, Scott; Iacono, William G.; Malone, Stephen M.
Abstract: Brain mechanisms linked to incorrect response selections made under time pressure during cognitive task performance are poorly understood, particularly in adolescents with attention‐deficit hyperactivity disorder (ADHD). Using subject‐specific multimodal imaging (electroencephalogram, magnetic resonance imaging, behavior) during flanker task performance by a sample of 94 human adolescents (mean age = 15.5 years, 50% female) with varying degrees of ADHD symptomatology, we examined the degree to which amplitude features of source‐resolved event‐related potentials (ERPs) from brain‐independent component processes within a critical (but often ignored) period in the action selection process, the stimulus‐response interval, were associated with motor response errors (across trials) and error rates (across individuals). Response errors were typically preceded by two smaller peaks in both trial‐level and trial‐averaged ERP projections from posterior medial frontal cortex (pMFC): a frontocentral P3 peaking about 390 ms after stimulus onset, and a premovement positivity (PMP) peaking about 110 ms before the motor response. Separating overlapping stimulus‐locked and response‐locked ERP contributions using a "regression ERP" approach showed that trial errors and participant error rates were primarily associated with smaller PMP, and not with frontocentral P3. Moreover, smaller PMP mediated the association between larger numbers of errors and ADHD symptoms, suggesting the possible value of using PMP as an intervention target to remediate performance deficits in ADHD. Abstract : Brain mechanisms that lead to increased probability of error commissions during speeded actions (≈0.5 s) and in individuals with attention‐deficit hyperactivity disorder (ADHD) remain unclear. In a group of adolescents with varying levels of ADHD symptoms, we examined whether brain potentials were associated with errors during the stimulus‐response interval in a visual selective attention task. Smaller Premovement Positivity (PMP) from posterior medial frontal cortex (pMFC) preceded errors and mediated the association between larger numbers of errors and ADHD symptoms. Findings link error proneness to pMFC/small PMP and reveal a possible neurophysiological target for remediation of error proneness in ADHD.